Expression of sars-cov-2 k51a/s54a nsp7 protein in escherichia coli c41(de3) and escherichia coli bl21(de3) - Mazri, Nurul Alya (Universiti Sains Malaysia, 2025)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) relies on the RNA-dependent RNA polymerase (RdRp) complex, comprising NSP7, NSP8, and NSP12, for replication and transcription. Mutations in NSP7, such as K51A and S54A, disrupt interactions with NSP8 and NSP12, impairing polymerase activity and structural integrity. These mutations offer insights into the development of antiviral therapeutics targeting the RdRp complex. This study aimed to express the mutant K51A/S54A NSP7 protein in Escherichia coli C41(DE3) and BL21(DE3) using the pET-15(b) vector. The methodologies included the preparation of the pET-15(b)-mutant NSP7 plasmid construct, transformation of the plasmid into E. coli, and optimization of protein expression. Parameters such as IPTG concentrations (0–1.0 mM) and different host strains were systematically optimized. The mutant NSP7 (K51A/S54A) protein was successfully expressed in both E. coli strains, with SDS-PAGE revealing distinct bands at the expected molecular weight. Optimal protein expression was achieved at 0.5 mM IPTG concentration. The findings highlighted differences in expression efficiency between E. coli C41(DE3) and E. coli BL21(DE3), with E. coli BL21(DE3) yielding higher expression levels. This research contributes to the understanding of SARS-CoV-2 replication by providing optimized conditions for expressing K51A/S54A NSP7 protein, enabling functional and structural studies. The findings offer a foundation for exploring NSP7 mutations as therapeutic targets and demonstrate the utility of bacterial systems for producing viral proteins in high yield, potentially accelerating antiviral drug discovery